Are Local Public Health Department Services Related to Racial Disparities in Mortality?. (18th March 2014) - Bekemeier, Betty; Grembowski, David; Yang, Youngran; Herting, Jerald R.
Our study aim was to determine whether local health department (LHD) services were associated with U.S. racial disparities in 1993-to-2005 mortality rates. In a national sample of LHDs, we examined 10 LHD service domains and gaps in Black–White all-cause mortality rates, drawing data from the National Association of County and City Health Officials' National Profile of Local Health Departments surveys, as well as mortality and other public data files. Two service domains, maternal/child health and other activities, were significantly associated with decreases in the Black–White mortality gap for 15- to 44-year-olds. The health services domain approached significance in decreasing this gap. Screening was associated unexpectedly with a significant increase in the Black–White mortality gap for 15- to 44-year-olds. Selected LHD services that are provided directly to individuals and are allocated by need may have particular benefit for reducing Black–White mortality disparities for U.S. adults aged 15 to 44.